Assessment of comorbidities and prognosis in patients with COPD diagnosed with the fixed ratio and the lower limit of normal: a systematic review and meta-analysis - Xiong, Huaiyu (Respir Res, 2020)
BACKGROUND: Currently, the diagnosis of chronic obstructive pulmonary disease (COPD) is not uniform, COPD guidelines recommend fixed ratio (FR), whereas ATS and ERS define airflow obstruction based on lower limit of normal (LLN). We aim to determine if there is difference between the two diagnostic criteria for morbidity, mortality, exacerbation. METHODS: Four databases and all relevant studies from the references were searched from inception to June 25, 2019, to find studies that described the rate of comorbidity, the exacerbation rates, mortality in COPD patients. Data analysis was performed using STATA/SE 14.0 and followed the standard of Cochrane Collaboration. A sensitivity analysis was performed to find the source of heterogeneity. RESULTS: Thirteen studies and 154,447 participants were finally included in this meta-analysis. The 11 cohort studies and 2 cross-sectional studies were all high-quality. Patients with airflow limitation according to either FR or LLN had higher mortality (HR(FR+/LLN-) = 1.27, 95% CI = 1.14–1.42; HR(FR−/LLN+) = 1.83, 95% CI = 1.17–2.86) than those who met neither criteria. When compared with the FR−/LLN- criteria, those who met the FR criteria were more likely to exacerbate (HR (FR+/LLN-) = 1.64, 95% CI = 1.09–2.46; HR (FR−/LLN+) = 1.58, 95% CI = 0.70–3.55). The meta-analysis for comorbidities showed no significant difference between patients who met neither criteria and those who met LLN or FR criteria. CONCLUSION: The patients with airflow limitations according to FR were more likely to exacerbate than those with LLN only. Patients that met either FR or LLN were more likely to have higher mortality than FR−/LLN-. There was no difference between the FR+/LLN- and FR−/LLN+ groups for the occurrence of comorbidities.